Polymorphous low-grade adenocarcinoma: a report of two cases - Rappoport, Daniel A.; Avayú, Tania; Burgoa, Antonio A.; Gac, Patricio J.; Rodríguez, Francisco J.; Vásquez, Loreto A.; Parada, Vivian A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Polymorphous low-grade adenocarcinoma (PLGA) is an infrequent type of malignant epithelial tumor that occurs almost exclusively in minor salivary glands. It commonly presents in women between the sixth and eighth decade of life, usually as an asymptomatic mass of long evolution and slow growth in the oral cavity but can erode and infiltrate adjacent bone. We present 2 case reports and review the literature on the subject. One case presented with a growing mass that developed over the course of 12 years, incorrectly diagnosed in the first incisional biopsy as a benign tumor. The second case presented as a recurring PLGA 19 years after the first, which appeared at an unusually young age. Both cases were managed with the treatment of choice: surgery with wide excision margins. Although prophylactic neck dissection is not the rule, it was part of the postoperative treatment in both cases, along with life-long follow-ups to find recurrences at early stages. A high level of suspicion and knowledge regarding its presentation are essential for correct diagnosis and management.